Enhanced routing for secured ad-hoc network - U Kumaran; A Ramachandran; J Jegan; E.K. Subramanian (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
A self-configured network forming an arbitrary topology of mobile routers through wireless connection is commonly referred as MANET (mobile ad-hoc network).  Random movement of routers allows the network to organize arbitrarily hence rapid unpredictable changes may occur in the topology of the wireless network. When there is no possibility of setting up permanent networks, MANETs are set up for carrying out the operations temporarily. As there is no fixed frame for this system, usage of available resources for reliable communication is a great challenge for MANETs. The nodes participating in packet routing in ad-hoc networks faces security issues such as maintaining the confidentiality of the packets, integration, availability of the network to meet the traffic, requirement of authentication for reliable data communication etc. Dropping of packets maliciously in an attack is known as black hole attack.An attempt is made in this paper to detect dynamically using the security of cross layer called as honeypot and classify the mechanisms to understand the strengths & threats of the protocols used for routing to suggest a concrete solution for the problems related to the mobile ad-hoc networks. The methodology of honeypot detects and isolates the attacks of the black hole. The results prove better delivery of packets with decreased load of the network.